Comparación del efecto antibacteriano de tres tipos de miel sobre el Streptococcus mutans (ATCC® 25175™) - Silva, CF. (2018)
ABSTRACT Objective: To compare the in vitro antibacterial effect of samples of Apis mellifera honey produced in Costa, Sierra and Selva against Streptococcus mutans ATCC 25175. Material and methods: The effect was evaluated in 3 groups distributed in concentrations of 100%, 50 % and 25% for each honey. Five repetitions were made per experimental group. The bacterial sensitivity was evaluated by the well diffusion method. The bacterial specimen was reactivated in nutritious broth, to inoculate it in heart agar culture. Results: When facing the microorganism to the honeys of bee, average halos were obtained of inhibition of 27,84 mm and 14,38 mm for the concentrations of 100% and 50% of the honey of bee of origin of saw. Conclusion: nevertheless, bee honeys of coastal and jungle origin did not present inhibition halos. It is concluded that bee honey of Sierra origin at 100% and 50% have antibacterial effect on S. mutans ATCC 25175